Identification and Validation of Entrepreneurial University Model Indicators for the University of Tabriz - Rostami , Parivash; Habibi , Hamdullah; Daneshvar Heris , Zarrin; Maleki Avarsin, Sadegh; Yari Haj Ataloo, Jahangir (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The aim of this research is to identify and validate the indicators of the entrepreneurial university model for the University of Tabriz. Methodology: The research methodology is a mixed-methods approach. This research is applied in terms of its objective and descriptive-survey in terms of data collection. The statistical population of the study included all the elites in the field of entrepreneurship at the University of Tabriz, all faculty members of the University of Tabriz, and all employees of the University of Tabriz, totaling 1,557 individuals. For sampling in the qualitative section, 14 individuals were selected using a purposive sampling method, and in the quantitative section, 308 individuals were selected using the Krejcie-Morgan table and simple random sampling. Data collection tools included researcher-constructed open-ended questions in the qualitative section and a researcher-constructed questionnaire, designed based on qualitative research results, in the quantitative section. For data analysis, coding methods were used in the qualitative section. In the quantitative section, the Kolmogorov-Smirnov test was used to check the normality of variable distributions; the one-sample t-test was used to determine the level of core category, main, and sub-components; and second-order confirmatory factor analysis was used to examine construct validity and model validation. Findings: The findings from inductive content analysis indicated that the entrepreneurial university model comprises fourteen main factors classified into four general categories: knowledge application factors, human factors, managerial factors, and environmental factors. Model validation results using the AMOS test showed that the extracted model from the present research had a good fit. Conclusion: The findings indicate that the developed model, comprising 14 main components categorized into four major factors—knowledge application, human, managerial, and environmental—has a good fit and is effective for transforming the University of Tabriz into an entrepreneurial university. This model can also be cautiously applied to other universities, considering their specific conditions and criteria.